The Effect of Superior and Inferior Extremity Point Acupuncture Therapy on Improving Daily Living Activities in Stroke Patients - Dodik Hartono; Rizka Yunita; Erna Handayani (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stroke is a pathological condition that occurs due to the interruption or reduction of blood flow to certain parts of the brain. This condition can be caused by two main mechanisms: blockage of cerebral blood vessels or the sudden rupture of blood vessels in the brain. As a result, there is a significant decrease in the supply of oxygen and nutrients to the affected brain tissue. One of the common symptoms of stroke is weakness on one side of the body, known as hemiparesis, which leads to difficulties in performing activities of daily living (ADL). This study aimed to analyze the effect of acupuncture therapy (at superior and inferior extremity points) on improving activities of daily living (ADL) in stroke patients at the Holistic Nursing Therapy Clinic in Probolinggo. The research method used was a pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 91 respondents, selected using accidental sampling from May to June 2025. The research instrument used was the Barthel Index questionnaire sheet, with a validity value of r > (0,4438) and a reliability test of (0,884). The intervention was administered three times per week, with each session lasting one hour, for four weeks. Data were analyzed using the Wilcoxon test. The results showed that before the acupuncture therapy intervention, most respondents were in the moderate category (42 respondents, 46.2%). After the intervention, respondents were mostly in the independent and mild categories, each with 39 respondents (42.9%). The statistical analysis indicated that there was a significant effect of acupuncture therapy (at superior and inferior extremity points) on improving activities of daily living (ADL) in stroke patients, with a p-value of 0.001 (p = 0.001 < α = 0.05). Acupuncture therapy has a positive impact on patients’ physical condition, including improving muscle strength in extremities that were weakened due to stroke. It may also enhance blood flow and oxygenation to the brain, promote neuroplasticity and nerve regeneration, and ultimately improve the ability to perform activities of daily living.